Daur al Mawāqi’ al Iliktrūniyah fī’ ‘Amaliyah al-Tarjamah min al-Lughah al-‘Arabiyah ila al-Lughah al-Indonesia wa Fa’āliyatuha (Muqāranah bayna Bing Translator wa ChatGPT) - Khoirurrosi, Khoirurrosi; Sa'adi, Zainur Rohmah (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2024)
Purpose- This study aims to determine the effectiveness of using the Bing Translator and ChatGPT websites in translating Arabic text into Indonesian using the lyrics of the song "Haawil Marroh Ukhro" by Humood al-Khudr as the translation instrument. Design/Methodology/Approach- The study employs a comparative method and adapted analysis of translation errors. Data collection involves translating lyrics using both applications, literature review, and translation references. Data analysis techniques include qualitative descriptive data analysis. Findings- The study indicates a comparative and adapted analysis of translation errors. Data collection involves translating lyrics using both applications, literature review, and translation references. Data analysis techniques include qualitative descriptive data analysis. Research Limitation/Implications- This study focuses on the Bing Translator and ChatGPT websites for translating the lyrics of the song "Haawil Marroh Ukhro" by Humood al-Khudr from Arabic into Indonesian.